Occupational Stress in Landing Platform Dock (LPD) Project Workers of PT. PAL Indonesia - Nunung Dwi Radanny; Sho’im Hidayat (Universitas Airlangga, 2019)
Introduction: Occupational stress is a condition in which the body responds physiologically, psychologically, and also behaviorally towards stressor. It can have negative effect on the workers and the workplace. The objective of this research is to study occupational stress and factors related to it in workers at Landing Platform Dock (LPD) project, especially Merchant Ship Division of PT PAL Indonesia. Methods: this research is an observational descriptive research. The subjects of the research are all the 32 workers of the project. The variables are occupational stress, individual characteristic, and work environment. Data was analyzed to discover the correlation between variables using contingency coefficient and Spearman correlation. Results: of the total 32 workers, 21.8% suffer from mild stress, 68.8% suffer from moderate stress, and 9.4% suffer from severe stress. Statistical test results show that there is a moderate correlation between level of education (coefficient -0.446), workload (coefficient 0.533), and relationship at work (coefficient 0.494) toward occupational stress. Meanwhile, personality factor (coefficient 0.334) and marital status (coefficient 0.231) have a weak impact on occupational stress. Furthermore, age (coefficient 0.146) has an extremely weak impact on occupational stress. Conclusion: factors that highly contributes to occupational stress are education level, workload, and relationship at work. Other factors such as age, personality type, and marital status only have a small correlation with occupational stress in these workers.Keywords: individual characteristic, occupational stress, work environment